2018
DOI: 10.1177/2329048x18773498
|View full text |Cite
|
Sign up to set email alerts
|

Afebrile Benign Convulsion Associated With Mild Gastroenteritis

Abstract: Background:Benign convulsion with mild gastroenteritis is a new clinical entity that occurs in children who are otherwise healthy.Method:This cohort study held among patients with afebrile convulsion and accompanying gastroenteritis in a tertiary children hospital during a 2-year period. Demographic and clinical data were analyzed. Neurodevelopmental milestones were observed during a follow-up period of 12 to 24 months.Results:Twenty-five patients aged 3 to 48 months with female predominance were enrolled. Nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…As reported previously, repetitive seizures are a unique characteristic of CwG, with a reported prevalence of 33-75% among these patients. [19][20][21] The current results indicate that severe ketosis is not significantly associated with seizure recurrence in the ED in comparison with nonsevere ketosis (53.3% vs. 37.0%, p=0.307), or with the risk of such recurrence (OR= 1.943, p=0.309). Although ketosis during a ketogenic diet achieves seizure reduction in children with refractory epilepsy, it is unknown whether elevated ketones directly inhibit seizures.…”
Section: Jcnmentioning
confidence: 47%
“…As reported previously, repetitive seizures are a unique characteristic of CwG, with a reported prevalence of 33-75% among these patients. [19][20][21] The current results indicate that severe ketosis is not significantly associated with seizure recurrence in the ED in comparison with nonsevere ketosis (53.3% vs. 37.0%, p=0.307), or with the risk of such recurrence (OR= 1.943, p=0.309). Although ketosis during a ketogenic diet achieves seizure reduction in children with refractory epilepsy, it is unknown whether elevated ketones directly inhibit seizures.…”
Section: Jcnmentioning
confidence: 47%
“…All children showed normal psychomotor development. Therefore, prescription of long-term antiepileptics is not recommended [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…BCWG seizures are often clustered, with generalized tonic-clonic seizures forming the most common type of seizure cluster, although focal or secondary generalized seizures are also observed [ 7 , 12 , 15 ]. Consistent with previous reports, we found that tonic or generalized tonic-clonic seizures were the most common types of seizures associated with BCWG; however, it is very likely that BCWG originated as a focal event as spikes were observed in the EEG tests that were localized to various regions of the cortex.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Interestingly, cluster seizures are also highly frequent in benign convulsions with mild gastroenteritis (CWG), which is a common cause of afebrile convulsions in children. [3] According to previous studies, Cluster seizures were observed in 13%-75% of patients with CWG. [4][5][6] With the absence of a previous history of convulsions in children with CWG, cluster seizures early in the course of this disease can easily cause anxiety in the family.…”
Section: Introductionmentioning
confidence: 93%